Evaluación de los factores físicos en el proceso de incubación de huevos y las características biológicas de la codorniz (coturnix coturnix) - Vera Troya, Carlos Alfredo (2024)
This research was developed at the Technical University of Babahoyo, faculty of agricultural sciences, located in the province of Los Ríos, in the Babahoyo Canton, with the objectives of analyzing the physical factors (laying time, size, weight and color of the egg). What quail eggs must have to guarantee good incubation and hatching, as well as Determine the biological characteristics of quails during the first week of life (Percentage of eggs hatched, Initial Weight, Weight after 8 days of study, Food Consumption , Feed Conversion, Weight Gain and Mortality) and Identify the Benefit/Cost relationship of the complete diet for feeding quail. The physical factors in the egg incubation process and the biological characteristics of the quail (coturnix coturnix) were evaluated, they were distributed under a completely randomized design (DCA), with a 3*3 bifactor arrangement, the experimental results that were obtained were subjected to the comparison of means according to Tukey at the significance levels of p < = 0.05 and p < = 0.01. To determine the profitability of the treatments, the Benefit/Cost Ratio was used. For its development, 270 quail eggs (coturnix coturnix) were used, which were distributed by laying time in 3, 6 and 9 days and according to their Size in Large, Medium and Small. Regarding the study variables, eggs with physical characteristics such as average weight of 14.07g; Big size; Intense and Punctate Color and Laying Time of 3 days were the key factor in the incubation phase, hatching and biological characteristics of the chicks. Obtaining an average initial weight of 7.83g; Co. Food 66.09g; Feed Conversion 1.7; Average weight gain of 32.11g; Mortality Percentage 9.7% and Benefit Cost of 2.40, study variables that decrease in eggs with laying time of 6 and 9 days.